Analysis of Knowledge with Compliance in Implementing Protocols of COVID-19 in SMP Negeri 4 Sukoharjo’s Students - Bangkit Ary Pratama; Sri Saptuti Wahyuningsih (P3M Universitas 'Aisyiyah Surakarta, 2022)
ABSTRACTEfforts to prevent the spread and increase in the number of COVID-19 sufferers were the implementation protocol of. Many people do not consistently implement it. Compliance in protocol of COVID-19 was absolutely a prerequisite for breaking the chain of transmission of COVID-19. This study aims to analyze knowledge with compliance in applying the protocols of COVID-19 in SMP Negeri 4 Sukoharjo’s students. This research was a quantitative research with the type of correlation research. The population in this study were all students at SMP Negeri 4 Sukoharjo, totaling 766 students. The sample size were 50 students that used accidental sampling. The primary data source used the results of the questionnaire answers that have been tested for validity and reliability and the data analysis used Pearson Product Moment. The results of the statistical test showed p-value (<0.001)<0.05, which means that there was a significant relationship between knowledge and compliance in implementing protocols of COVID-19.Keywords: knowledge; compliance; protocol of COVID-19